THY-1 Receptor Expression Differentiates Cardiosphere-Derived Cells with Divergent Cardiogenic Differentiation Potential - Gago-Lopez, Nuria (Elsevier, 2014)
Despite over a decade of intense research, the identity and differentiation potential of human adult cardiac progenitor cells (aCPC) remains controversial. Cardiospheres have been proposed as a means to expand aCPCs in vitro, but the identity of the progenitor cell within these 3D structures is unknown. We show that clones derived from cardiospheres could be subdivided based on expression of thymocyte differentiation antigen 1 (THY-1/CD90) into two distinct populations that exhibit divergent cardiac differentiation potential. One population, which is CD90(+), expressed markers consistent with a mesenchymal/myofibroblast cell. The second clone type was CD90(−) and could form mature, functional myocytes with sarcomeres albeit at a very low rate. These two populations of cardiogenic clones displayed distinct cell surface markers and unique transcriptomes. Our study suggests that a rare aCPC exists in cardiospheres along with a mesenchymal/myofibroblast cell, which demonstrates incomplete cardiac myocyte differentiation.